Investigating donor behavior in fundraising activities - Koh, Joshua Shi Kai (2016)
Many factors cause donor behaviour to vary. While working with the Singapore Red Cross Society, it is seen that there is a disparity between donations given to international disaster relief and local beneficiaries, with local projects usually getting less support. This project attempts to look at how age, gender and income may affect donor behaviour in 6 different scenarios. The scenarios discussed are 1. Willingness to donate when the plea is emotional versus factual, 2. Willingness to donate to international disaster relief versus local beneficiaries, 3. Preference of ways an organization can encourage donors to give recurring donations, 4. Preference of type of beneficiary, 5. Preference of type or form of the donations and 6. Understanding of the Singapore Red Cross and handling of their funds. To get an understanding of donor behaviour in Singapore, data was gathered through a survey with a total of 301 respondents. Analysis of the data was done using IBM’s SPSS software to run statistical tests which included the Mann-Whiney U-test, the Kruskal-Wallis H-Test, the Chi Squared test of independence and the odds ratio. From the results, it was seen that age played a part in determining how a respondent reacts to recurring donations and carnival type of events. It was seen that the chance of a respondent being willing to give recurring donations increases with age. Also, carnivals appealed mainly to those in the 15 to 24 years old age band. Income played a part in determining if the respondent was willing to donate to homes for the disabled and if the respondent had an understanding of the SRCS’s main goals. It was seen that high income group was more willing to donate to homes for the disabled as well as have a larger percentage within the income group that has an understanding of what the SRCS’s main goal is. About gender, it was seen that females tend to be more willing to donate to charitable causes regardless of the type of plea or whether the cause was for local and international bodies. It was also seen that females were twice as likely to donate to projects involving medication for the disadvantaged. Regardless of age, gender and income, it was seen that the respondents are more willing to make a donation to local beneficiaries as compared to their willingness to donate to international disaster relief. However, it was also seen that people do not have a good understanding of the SRCS’s main goals as well as how funds for local projects and international ones are handled, which may have led to the difference in amounts raised for local beneficiaries when compared to disaster relief projects. A significance level of 0.1 was selected for this project and only results with statistical significance were further discussed and analysed.